Panoply of microbial protein production in ruminants – A review - SRINIVAS, BANDLA; KRISHNAMOORTHY, U (The Indian Journal of Animal Sciences, 2013)
Microbial protein (MBP) production plays a pivotal role in ruminant nutrition. Any improvement in the quantitative production of MBP in rumen can resolve simple to complex issues such as digestibility to methanogensis. Quantitative aspects of rumen microbial biomass are important than qualitative milieu present in rumen for functional expression of nutrition to the health and productivity of host animal. Functional biodiversity observed in the rumen microorganism isÂ well orchestrated adaptation between various subpopulations. Magnificent array of biological, physical and chemical factors involved in MBP production and its efficiency are discussed in this review.